Nutritional risk screening (NRS 2002) is a strong and modifiable predictor risk score for short-term and long-term clinical outcomes: secondary analysis of a prospective randomised trial. Issue 9 (September 2020) - Hersberger, Lara; Bargetzi, Laura; Bargetzi, Annika; Tribolet, Pascal; Fehr, Rebecca; Baechli, Valerie; Geiser, Martina; Deiss, Manuela; Gomes, Filomena; Kutz, Alexander; Kägi-Braun, Nina; Hoess, Claus; et al.
Summary: Introduction: The Nutritional Risk Screening 2002 (NRS 2002) identifies patients at risk of malnutrition. We studied the prognostic implications of this score with regard to short-term and long-term clinical outcomes in a well-characterised cohort of medical inpatients from a previous trial. Methods: This is a secondary analysis of an investigator-initiated, prospective randomised controlled multicenter trial in Switzerland (EFFORT) that compared the effects of an individualised nutritional support intervention with standard of care. We investigated associations between admission NRS and several short-term and long-term outcomes using multivariable regression analyses. Results: Of the 2028 patients, 31% had an NRS of 3, 38% of 4 and 31% of ≥5 points, and 477 (24%) died during the 180 days of follow-up. For each point increase in NRS, we found a stepwise increase in risk of 30-day mortality (adjusted Hazard Ratio (HR) 1.22 (95% CI 1.00 to 1.48), p = 0.048) and 180-day mortality (adjusted HR 1.37 (95% CI 1.22 to 1.55), p < 0.001). NRS was associated with length of hospital stay (adjusted difference of 0.60 days per NRS point increase, 95%CI 0.23 to 0.97, p = 0.002) and functional outcomes at 180 days (adjusted decrease in Barthel index of −4.49 points per NRS point increase, 95%CI -6.54 to −2.45, p < 0.001). In a subgroup analysis, associations of NRS and short-term adverse outcomes were less pronounced in patients receiving nutritional support (intervention group) compared to control group patients (adjusted HR for 30-day mortality 1.12 [95%CI 0.83 to 1.52, p = 0.454] vs. 1.33 [95%CI 1.02 to 1.72, p = 0.032]). Conclusion: The NRS is a strong and independent risk score for malnutrition-associated mortality and adverse outcomes over 180 days. Our data provide strong evidence that the nutritional risk, however, is modifiable and can be reduced by the provision of adequate nutritional support.